Complement Expression and Activation in Osteoarthritis Joint Compartments - Assirelli, Elisa; Pulsatelli, Lia; Dolzani, Paolo; Mariani, Erminia; Lisignoli, Gina; Addimanda, Olga; Meliconi, Riccardo (Frontiers in Immunology, 2020)
Objective. To investigate complement(C) factors(F) and their activation fragments expression in OA joint tissues. Design. Immunohistochemistry and quantitative Imaging were performed to analyze C3, C4 and CF (factor) B expression on osteochondral biopsies (43 patients) collected during arthroplasty. Isolated chondrocytes and synoviocytes, cartilage and synovial tissues obtained from surgical specimens of OA patients (15 patients) were cultured with or without IL-1β. Real time PCR for CFB, C3 and C4 was performed. Culture supernatants were analysed for C3a, C5a, CFBa and Terminal Complement Complex (TCC) production. Results. In osteochondral biopsies, C factor expression was located in bone marrow, in a few subchondral bone cells and chondrocytes. C3 was the most expressed while factor C4 was the least expressed factor. Gene expression showed that all C factors analyzed were expressed both in chondrocytes and synoviocytes. In chondrocyte cultures and cartilage explants, CFB expression was significantly higher than C3 and C4. Furthermore, CFB, but not C3 and C4 expression was significantly induced by IL-1β. As to C activation factors, C3a was the most produced and CFBa was induced by IL-1β in synovial tissue. TCC production was undetectable in isolated chondrocytes and synoviocytes cell culture supernatants whereas it was significantly augmented in cartilage explants. Conclusion. C factors were locally produced and activated in OA joint with the contribution of all tissues (cartilage, bone and synovium). Our results support the involvement of innate immunity in OA and suggest an association between C alternative pathway and IL-1beta inflammatory cytokine.